2022
DOI: 10.1007/s10902-022-00578-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Three-Stage Strength-Based Meaning Intervention to Promote Mental Health Among Individuals with Physical Disabilities in Disadvantaged Communities: A Randomized Controlled Trial

Abstract: A three-stage strength-based meaning intervention (SMI) was developed in the present study, and its utility in facilitating the mental health of individuals with physical disabilities in low-income communities was tested. A randomized controlled and single-blind trial was adopted. A total of 50 qualified participants (mean age = 42.12, standard deviation = 8.68; 48% males; 26 for the intervention group, 24 for the control group) completed the pre-intervention test, post-intervention test, and three-month follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
1
0
1
Order By: Relevance
“…En concordancia con la afirmación anterior, la logoterapia desde una mirada en la educación, emerge en temas; como, el estrés académico direccionando a la formación de la identidad en alumnos en educación escolar tardía (Lim, 2022); en trastornos mentales por estrés en estudiantes universitarios (Fereydouni & Forstmeier, 2022); en personas con discapacidades físicas de bajos recursos económicos (Duan et al, 2022); en la identidad de adultez emergente (Sanli & Ersanli, 2021); en la comunicación efectiva para la relación entre padres e hijos autistas (Mihandoust et al, 2021); en poblaciones expuestas al riesgo de salud mental asociados por la inmigración y el asilo (Rahgozar & Giménez-Llort, 2020); en prisioneros de la guerra de Iraní, quienes tenían que pasar su tiempo en lo desagradable, y a menudo en circunstancias insoportables en estos campos (Emam, 2018); en mujeres reclusas que se encuentran en los grupos más vulnerables de la sociedad, frecuentemente con antecedentes de daños sociales, laborales y familiares (Ghelbash et al, 2020).…”
Section: Resultados Y Discusiónunclassified
“…En concordancia con la afirmación anterior, la logoterapia desde una mirada en la educación, emerge en temas; como, el estrés académico direccionando a la formación de la identidad en alumnos en educación escolar tardía (Lim, 2022); en trastornos mentales por estrés en estudiantes universitarios (Fereydouni & Forstmeier, 2022); en personas con discapacidades físicas de bajos recursos económicos (Duan et al, 2022); en la identidad de adultez emergente (Sanli & Ersanli, 2021); en la comunicación efectiva para la relación entre padres e hijos autistas (Mihandoust et al, 2021); en poblaciones expuestas al riesgo de salud mental asociados por la inmigración y el asilo (Rahgozar & Giménez-Llort, 2020); en prisioneros de la guerra de Iraní, quienes tenían que pasar su tiempo en lo desagradable, y a menudo en circunstancias insoportables en estos campos (Emam, 2018); en mujeres reclusas que se encuentran en los grupos más vulnerables de la sociedad, frecuentemente con antecedentes de daños sociales, laborales y familiares (Ghelbash et al, 2020).…”
Section: Resultados Y Discusiónunclassified
“…Although positive psychology is a relatively young branch of psychology, a few strengths-based intervention studies were conducted (Gander et al, 2012;Duan et al, 2018;Bu and Duan, 2019), and the number of publications was increased in recent years. Part of the existing studies demonstrated the effectiveness of strengths-based interventions (Duan et al, 2013(Duan et al, , 2022bCarr et al, 2020), while others constructed and examined the validation of character strengths-based interventions (Niemiec, 2018;Duan et al, 2022a). However, research on how and why these strengths-based interventions work remains unclear (Ghielen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%